2011
DOI: 10.1002/stem.761
|View full text |Cite
|
Sign up to set email alerts
|

Myb Controls Intestinal Stem Cell Genes and Self-Renewal

Abstract: Rapid advances have been made in the understanding of how the highly proliferative gastrointestinal tract epithelium is regulated under homeostasis and disease. The identification of putative intestinal stem cell (ISC) genes and the ability to culture ISC capable of generating all four lineages plus the architecture of small intestinal (SI) crypts has been transformative. Here, we show that transcription factor Myb governs ISC gene expression, particularly Lgr5. Lgr5 is associated with cells that have the capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…We have previously shown that cell-cycle re-entry, progression, and proliferation appear retarded within the colonic crypts of Myb Plt4/Plt4 hypomorphic mutant mice, which correlated with a significant reduction in Ccne1 expression (14,15). These data suggested that the cell-cycle defects observed in the Myb hypomorphs may be due, in part, to reduced Ccne1 expression.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…We have previously shown that cell-cycle re-entry, progression, and proliferation appear retarded within the colonic crypts of Myb Plt4/Plt4 hypomorphic mutant mice, which correlated with a significant reduction in Ccne1 expression (14,15). These data suggested that the cell-cycle defects observed in the Myb hypomorphs may be due, in part, to reduced Ccne1 expression.…”
Section: Introductionmentioning
confidence: 88%
“…The propagation and derivation of CT26, MC38, YAMC, and NIH3T3 cell lines have been described in detail elsewhere (14). Lentiviral small hairpin RNA particles (CyclinE1; NM007633/ TRCN0000077777) were purchased from Sigma.…”
Section: Cell Lines Tumor Cell Injections and Shrnamentioning
confidence: 99%
See 3 more Smart Citations